Immunogenicity and Effectiveness of Routine Immunization With 1 or 2 Doses of Inactivated Poliovirus Vaccine: Systematic Review and Meta-analysis - Grassly, Nicholas C. (Oxford University Press, 2014)
Background. The World Health Organization has recommended that all 124 countries currently using only oral poliovirus vaccine (OPV) introduce at least 1 dose of inactivated poliovirus vaccine (IPV) before the global withdrawal of serotype 2 OPV in 2016. A 1- or 2-dose schedule, potentially administered intradermally with reduced antigen content, may make this affordable. Methods. A systematic review and meta-analysis of studies documenting seroconversion after 1 or 2, full or fractional (1/5) doses of enhanced-potency IPV was performed. Studies reporting the clinical efficacy of IPV were also reviewed. Results. Twenty study arms from 12 published articles were included in the analysis of seroconversion. One full dose of intramuscular IPV seroconverted 33%, 41%, and 47% of infants against serotypes 1, 2, and 3 on average, whereas 2 full doses seroconverted 79%, 80%, and 90%, respectively. Seroconversion increased with age at administration. Limited data from case-control studies indicate clinical efficacy equivalent to the proportion seroconverting. One fractional dose of intradermal IPV gave lower seroconversion (10%–40%), but after 2 doses seroconversion was comparable to that with full-dose IPV. Conclusions. Routine immunization with 2 full or fractional doses of IPV given after 10 weeks of age is likely to protect >80% of recipients against poliomyelitis if poliovirus reemerges after withdrawal of OPV serotypes.